Enhancing Students' Mathematical Interpretation Ability through Project-Based Learning in Statistics: Evidence from a Quasi-Experimental Study - Syauqi Fari Hapittullah; Ratu Sarah Fauziah Iskandar; Rika Sukmawati; Muhammad Hafeez (Edupedia Publisher, 2026)
Purpose – Mathematical interpretation ability is a key component of mathematical literacy, enabling students to interpret mathematical representations and solve contextual problems. However, many junior secondary students struggle to interpret statistical information presented in pie charts. This study examined the effectiveness of Project-Based Learning (PjBL) in improving students' mathematical interpretation ability in statistics. Methodology – A quasi-experimental study using a non-equivalent control group design was conducted with 42 Grade VII students from MTs Al-Layyinah, Indonesia. The participants were assigned to an experimental group (n = 21) and a control group (n = 21). Data were collected using a six-item essay test and analysed through descriptive statistics, the Shapiro–Wilk test, Levene's test, and an Independent Samples t-test. Findings – Students in the experimental group outperformed those in the control group (74.05 vs. 64.05). The difference was statistically significant (t = 3.044, p = 0.004), indicating that PjBL effectively improved students' mathematical interpretation ability. Novelty – This study provides empirical evidence that authentic project activities integrating data collection, pie-chart construction, and contextual interpretation effectively develop mathematical interpretation ability in statistics. Significance – The findings support the integration of PjBL into mathematics instruction to strengthen students' mathematical interpretation ability and statistical literacy.